Magneto-hydrodynamic boundary layer flow and heat transfer of hybrid carbon nanotube over a moving surface - Azahari, A. A.; N., Bachok (Lviv Polytechni National University, 2023)
The boundary layer flow and heat transfer of hybrid carbon nanotubes over a moving surface with magneto-hydrodynamic effect are studied numerically in this paper. Single-wall (SWCNT) and multi-wall (MWCNT) carbon nanotubes are combined with water as the base fluid to form hybrid carbon nanotubes. The governing partial differential equations were transformed into a set of nonlinear ordinary differential equations using the similarity transformation, which were then numerically solved in the Matlab software using bvp4c. The influence of the nanoparticle volume fraction, magnetic parameter and velocity ratio parameter, on velocity and temperature profiles, local skin friction and local Nusselt number are discussed and presented in graphical forms. The results show that dual solutions appear when the free stream and plate move in the opposite direction, and the rate of heat transfer for hybrid carbon nanotubes is higher than viscous fluid and carbon nanotubes.